The Emergence of Halal Fashion: Empowering Women Entrepreneurs in Indonesia - Jimmi Qizwini; Husnul Khatimah; Hardiansyah Hardiansyah (Tazkia Islamic Finance and Business Review, 2024)
The rise of halal fashion in Indonesia has significantly shaped the modest fashion industry and provided a unique platform for women entrepreneurs to thrive. As global demand for modest and ethical fashion increases, Indonesia stands out as a leader, with its halal fashion brands spearheading both local and international markets. This study explores how the growth of Indonesia’s halal fashion industry has empowered women entrepreneurs by fostering economic opportunities, promoting cultural identity, and encouraging entrepreneurial innovation. The primary objective of the study is to assess how these women navigate the complexities of the halal fashion market while driving significant social and economic change. The novelty of this research lies in its focus on Indonesian women entrepreneurs, an underexplored segment in the global halal fashion landscape. While previous studies have examined the growth of halal fashion, few have focused on how women entrepreneurs are leveraging this industry for empowerment and socio-economic advancement. Using a qualitative case study approach, the research draws on secondary data from academic literature, industry reports, and media publications. It focuses on the impact of prominent Indonesian brands, such as Dian Pelangi, Shafira and Ria Miranda, highlighting their role in challenging societal norms and creating inclusive business models.The findings reveal that Indonesian halal fashion brands not only contribute to economic empowerment but also promote gender equality and cultural pride. These women-led businesses are reshaping the global modest fashion industry while providing a framework for future entrepreneurs.